Incest and Ancient Astrology - Pérez-Jiménez, Aurelio; Pérez-Jiménez, Aurelio (International Journal of Ancient Astrology and Magic Research, 2016)
In the ancient Graeco-Roman world the practice of incest, if one excepts myth and rarely historical context (for economic or political reasons), was in general considered out from the law and from the social conventions. In fact, heroic myths present incest as an aberration of fatal consequences for their practitioners, being the most notable example that of Oedipus. But that incest was practiced in Greek and Roman societies (and not only in oriental peoples as Egiptian and Persian where its tradition was well established) is evidenced by the astrological texts. Indeeed, astrologers, by transferring the responsibility of incest to the planets, exempted from ethical responsibility those who falled into such practices.